A Biopsychosocial Model for Understanding Media Internalization and Appearance Dissatisfaction Among Preadolescent Boys and Girls. (April 2020) - Rousseau, Ann; Rodgers, Rachel F; Eggermont, Steven
Sociocultural models emphasize the role of media internalization in preadolescents' appearance dissatisfaction. The present three-wave panel study sought to examine how biological, psychological, and sociocultural factors jointly contribute to preadolescents' ( N = 973, M age = 11.15 years) media internalization and appearance dissatisfaction over time. Structural equation modeling was conducted to test a hypothetical model in which media internalization mediated the effect of (a) pubertal timing, (b) media-related conversations with friends, and (c) perceptions of media as a good source of information regarding appearance and attractiveness, on change in appearance satisfaction. The model also examined the protective role of social self-esteem against the internalization of media ideals. For girls, pubertal timing was associated with increases in media internalization over time, directly and indirectly through media information and media-related conversations. For boys, pubertal timing indirectly predicted increases in media internalization over time, through media-related conversations. Media internalization positively predicted body dissatisfaction over time, and vice versa. Social self-esteem did not serve as a buffer against media internalization.